Cable slouches toward open access. - Ingebretsen, M.
Discusses the prospects for Internet open access over the cable networks. The technical and regulatory hurdles towards this goal are considered. Mention is made of policy based routing in particular
Keywords: Internet; Cable networks; Open access; Policy based routing; Regulatory hurdles; Technical hurdles